2019
DOI: 10.5334/gjgl.770
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the cognitive cost of downward monotonicity by controlling for negative polarity

Abstract: Our goal in this study was to behaviorally characterize the property (or properties) that render negative quantifiers more complex in processing compared to their positive counterparts (e.g. the pair few/many). We examined two sources: (i) negative polarity; (ii) entailment reversal (aka downward monotonicity). While negative polarity can be found in other pairs in language such as dimensional adjectives (e.g. the pair small/large), only in quantifiers does negative polarity also reverse the entailment pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Context cannot explain the well-known interaction of polarity with truth value: The polarity effect is smaller for false sentences (i.e., mismatch between sentence and picture) than it is for true sentences. This highly replicable finding suggests that truth value also is an important factor (Agmon et al, 2019;Carpenter & Just, 1975;Just & Carpenter, 1971;Krueger, 1972;Mac-Donald et al, 1992;Mayo et al, 2004;Tucker et al, 2018).…”
Section: The Processing Cost Of Negationmentioning
confidence: 85%
See 3 more Smart Citations
“…Context cannot explain the well-known interaction of polarity with truth value: The polarity effect is smaller for false sentences (i.e., mismatch between sentence and picture) than it is for true sentences. This highly replicable finding suggests that truth value also is an important factor (Agmon et al, 2019;Carpenter & Just, 1975;Just & Carpenter, 1971;Krueger, 1972;Mac-Donald et al, 1992;Mayo et al, 2004;Tucker et al, 2018).…”
Section: The Processing Cost Of Negationmentioning
confidence: 85%
“…A unified account that explains both the delayed effect of sentential negation and of negative quantifiers would be more parsimonious and hence desirable 8 . Currently, there is one such suggestion for a unified account: Both negations share the logical property of reversing entailment patterns, which adds to their representational complexity (Agmon et al, 2019; Deschamps et al, 2015). In the following examples, adding either sentential negation (Sentence 1b) or a negative quantifier (Sentence 1c) changes the direction of the logical entailment presented in Sentence 1a: 1a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of these studies agree that statements quantified by negative quantifiers are harder to process and are more error prone in comprehension compared to statements quantified by positive quantifiers. More recent research about the processing complexity of negative quantifiers showed that both (i) negative polarity and (ii) downward monotonicity are two logical properities that make the processing of negative quantifiers cognitively more complex relative to their positive antonyms (Agmon et al, 2019).…”
Section: Negation Polarity Monotonicity and Processingmentioning
confidence: 99%